An Efficient Access to Heteroaryl/Aryl-Annulated Pyridine Derivatives and a Study of Their Mosquito Larvicidal Activity Against Dengue Vector - Pal, Pamela; Show, Sayanti; Das, Sukanya; Bhakta, Sayantika; Mondal, Swarupa; Roy, Priya; Ghosh, Tapas; Nandi, Raj K. (Synlett, 2024)
We report a convergent synthesis of heteroaryl/aryl-annulated pyridine and quinoline derivatives by a metal-free Povarov reaction. para-Toluene sulfonic acid was used as the catalyst in this reaction, which produced the products in good yields from the corresponding aromatic amines and ethyl vinyl ether. A pyridocoumarin and a pyridopyrimidine product were evaluated for their mosquito larvicidal activity against the third instar larvae of the dengue vector mosquito Aedes aegypti. Examination of morphological changes in the larvae showed damage to the target body part after treatment with both the pyridocoumarin and pyridopyrimidine products at the LC50 concentrations.
Keywords: pyridocoumarins; pyridopyrimidines; Povarov reaction; metal-free synthesis; insecticides